Different mutational function of low‐ and high‐linear energy transfer heavy‐ion irradiation demonstrated by whole‐genome resequencing of Arabidopsis mutants. (15th November 2017) - Kazama, Yusuke; Ishii, Kotaro; Hirano, Tomonari; Wakana, Taeko; Yamada, Mieko; Ohbu, Sumie; Abe, Tomoko
Summary: Heavy‐ion irradiation is a powerful mutagen that possesses high linear energy transfer (LET). Several studies have indicated that the value of LET affects DNA lesion formation in several ways, including the efficiency and the density of double‐stranded break induction along the particle path. We assumed that the mutation type can be altered by selecting an appropriate LET value. Here, we quantitatively demonstrate differences in the mutation type induced by irradiation with two representative ions, Ar ions (LET: 290 keV μm −1 ) and C ions (LET: 30.0 keV μm −1 ), by whole‐genome resequencing of the Arabidopsis mutants produced by these irradiations. Ar ions caused chromosomal rearrangements or large deletions (≥100 bp) more frequently than C ions, with 10.2 and 2.3 per mutant genome under Ar‐ and C‐ion irradiation, respectively. Conversely, C ions induced more single‐base substitutions and small indels (<100 bp) than Ar ions, with 28.1 and 56.9 per mutant genome under Ar‐ and C‐ion irradiation, respectively. Moreover, the rearrangements induced by Ar‐ion irradiation were more complex than those induced by C‐ion irradiation, and tended to accompany single base substitutions or small indels located close by. In conjunction with the detection of causative genes through high‐throughput sequencing, selective irradiation by beams with different effects will be a powerful tool for forward genetics as well as studies on chromosomal rearrangements. Significance Statement: In the heavy‐ion irradiation, the value of linear energy transfer (LET) can be manipulated by the selection of ion species and particle velocity. Here, we show that the type of induced mutations is affected by the value of LET. Our findings will allow researchers to select the mutation spectrum depending on the purpose of their research.